Pengaruh Program Boarding School Terhadap Prestasi Belajar Tahfidz di SMP Islam Al Hadi Mojolaban Sukoharjo Tahun Ajaran 2023/2024 - Yuniati, Yuniati; Nashir, Ja’far; Amin, Lailla Hidayatul (Peneliti.net, 2024)
The Boarding School Program is considered as one of the factors that affect student achievement results in the classroom. Therefore, this study was conducted with the aim of knowing whether or not there is an effect of the boarding school program on students' tahfidz learning achievement in class. This study uses quantitative research. The sample selected was 56 students of Al Hadi Mojolaban Islamic Junior High School who lived in the boarding school. Data collection techniques were carried out by distributing questionnaires to boarding program students and documentation. The analysis technique used is a statistical technique to describe the results of the research conducted. To test the validity of the data, validity test and linearity test were used. The results showed that: 1) The Boarding School Program is categorized as good with a percentage of 67.85%. 2) The results of research on tahfidz learning achievement at Al Hadi Islamic Junior High School Mojolaban Sukoharjo are classified as sufficient with a percentage of 60.714%. 3) There is an influence between the boarding school program on Tahfidz learning achievement at Al Hadi Islamic Junior High School Mojolaban Sukoharjo as evidenced by hypothesis testing using the product moment correlation formula with a result of -0.141 but the correlation is very weak or very low so that this correlation is ignored or considered no correlation between variable X and variable Y. If rxy is compared with rtable at the 95% significance level of 0.266, then the alternative hypothesis is rejected and hypothesis 0 is accepted.